KERJA SAMA ANTARA PEMERINTAH DAERAH DAN PIHAK LUAR NEGERI (Perspektif Hukum Administrasi Negara) - Geraldine Renayanthi; Endra Wijaya (Program Magister Ilmu Hukum Universitas Pancasila, 2020)
The development of local region needs many resources, and one of them could be gainedthrough foreign country in the form of cooporation relationship between the LocalGovernment and the foreign party. Such kind of cooporation is reliable in the context ofdecentralization implementation in Indonesia. In the decentralization, the CentralGovernment devolves several powers to the Local Government, so with those powers, itcould manage its own needs based on its unique local condition. In the Indonesian legalsystem, the cooporation between the Local Government and the foreign party is ruledunder several acts and regulations, and the aims are to establish such cooporation workseffectively, efficiently, and not disturb the Indonesian system relating to the relationshipbetween the Central Government and the Local Government